Toxicological assessment of pesticides with the help of hydrobionts - Ісаєнко, В.М.; Давидова, К.О.; Гетнаревич, О.А. (Proceedings of National Aviation University (archive), 2005)
Experiments of toxic influence of insecticide novoverm (product of bio-technical synthesis) were held using the national stam of non-pathogenic fungi Streptomyces avermitilis and hexachloran on Daphnia magna. As a result of experimental data were calculated the main toxic characteristics: medial lethal concentrations LC50, non observed effective concentration LC0, and lethal concentration LC100 that allow determining the toxicity of pesticides in accordance with the International Eco-toxicological Classification Schemes of the World Health Organization. Insecticide novoverm is considered to be a “moderately toxic” substance; hexachloran is a “highly toxic” substance.